The possibilities of using the digital economy in monetary policy in developing countries: the case of Azerbaijan (Economics and region, 2024)
The widespread use and development of information technologies in modern times has led to the growth of the role of the digital economy in the overall world economy. Taking into account that information technology is fast and convenient, new methods have been developed based on its application in all areas. This change has not gone unnoticed by the economy. The implementation of the digital economy was addressed during the research. Digital economy refers to all economic components created by information technologies. This includes digital exchanges, blockchain technologies, web economy, cryptocurrencies, e-commerce, e-money, internet banking, digital marketing, etc. such components are attributed. When we take into account the current inflation situation in the world as well as the damages inflation has caused to the national economy throughout history, we can easily express how important the issue of combating inflation is. The main task in the fight against inflation falls to the monetary policies of countries. For this reason, this study evaluates the possibilities of creating a more sustainable economic policy in countries that utilize the modern capabilities of the digital economy. The issue of creating a more effective anti-inflation policy as a result of the application of the digital economy to monetary policy was discussed. The research is based on the economies of developing countries. Because developed countries are in a more advantageous position due to their technological and economic advantages. It would be more useful to look at the possibilities of utilizing the digital economy in developing countries. The Republic of Azerbaijan was chosen as a model developing country when evaluating the application of the digital economy to the country's economy. The issue was evaluated from the point of view of the state of economic policy and development opportunities of the Azerbaijani state, and the possibilities of using the digital economy in the monetary policy of combating inflation were investigated.
Keywords: digital economy; developing countries; monetary policy; inflation; anti-inflation